THE EFFECT OF FINANCIAL INCLUSION AND PEER TO PEER LENDING ON THE PERFORMANCE OF UMKM IN SUMATERA - Syaifuddin, Syaifuddin; Sugito, Sugito; Rosmaneliana, Dina (Jurnal Manajemen Dayasaing, 2024)
The increasing development of Micro, Small, and Medium Enterprises (MSME) will have a positive impact on the provision of labor. Therefore, it is important to continue to increase the number of MSME. his study will explain whether there is an influence of Financial Inclusion and Peer To Peer Lending on the Performance of MSME in Sumatra. Data collection uses quantitative methods and uses an explanatory research approach. The population of this study is MSME actors operating in the cities of North Sumatra. Sample selection uses the Slovin approach, so that a minimum sample size of 90 MSMEs is obtained. The results of the study show that financial inclusion has a positive effect on MSME performance. Likewise, Peer To Peer Lending also appears to have a positive effect on MSME workers in North Sumatra.